2013
DOI: 10.2337/dc13-0425
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Type 1 Diabetes by Multiple Autoantibody Levels and Their Incorporation Into an Autoantibody Risk Score in Relatives of Type 1 Diabetic Patients

Abstract: OBJECTIVEWe assessed whether a risk score that incorporates levels of multiple islet autoantibodies could enhance the prediction of type 1 diabetes (T1D).RESEARCH DESIGN AND METHODSTrialNet Natural History Study participants (n = 784) were tested for three autoantibodies (GADA, IA-2A, and mIAA) at their initial screening. Samples from those positive for at least one autoantibody were subsequently tested for ICA and ZnT8A. An autoantibody risk score (ABRS) was developed from a proportional hazards model that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 31 publications
1
77
0
1
Order By: Relevance
“…Once the child had developed dysglycemia, high-level IA-2A did not act as a strong additional risk factor for progression to type 1 diabetes. Hence, high-level IA-2A levels may not be an independent risk factor for progression to type 1 diabetes as previously reported [26,24] but rather be related to and precede dysglycemia observed prior to the clinical onset of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Once the child had developed dysglycemia, high-level IA-2A did not act as a strong additional risk factor for progression to type 1 diabetes. Hence, high-level IA-2A levels may not be an independent risk factor for progression to type 1 diabetes as previously reported [26,24] but rather be related to and precede dysglycemia observed prior to the clinical onset of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
“…High titres [24] as well as increasing titres [25] of IA-2 have previously been found to predict clinical onset of type 1 diabetes. We could confirm this finding in our young population of GAD65A positive children.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the risk of progression to type 1 diabetes from the time of seroconversion to autoantibody positivity in three pediatric cohorts from Finland, Germany, and the U.S. Of the 585 children who developed more than two autoantibodies, nearly 70% developed type 1 diabetes within 10 years and 84% within 15 years (19,20). These findings are highly significant because, while the German group was recruited from offspring of parents with type 1 diabetes, the Finnish and American groups were recruited from the general population.…”
Section: Testing For Type 1 Diabetes Riskmentioning
confidence: 99%
“…A recent study reported the risk of progression to type 1 diabetes from the time of seroconversion to autoantibody positivity in three pediatric cohorts from Finland, Germany, and the U.S. Of the 585 children who developed more than two autoantibodies, nearly 70% developed type 1 diabetes within 10 years and 84% within 15 years (16,18). These findings are highly significant because, while the German group was recruited from offspring of parents with type 1 diabetes, the Finnish and American groups were recruited from the general population.…”
Section: Testing For Type 1 Diabetesmentioning
confidence: 99%